Exploring the involvement of the characters with regards to: the pre-revolutionary atmosphere, during and after the French revolution in Dickens’ a Tale of Two Cities, Hugo’s Les Misérables and Baudelaire’s selective poems - Aftab, Rezwana (BRAC University, 2014)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Arts in English, 2013.